Предмет: Математика,
автор: r0150835
a) 5x + 3(x - 1) = 6x + 11; c) 8(y-7) - 3(2y + 9) = 15; e) 6+ (2 - 4x) + 5 = 3(1-3x);
Ответы
Автор ответа:
0
Відповідь:
Покрокове пояснення:
Приложения:
Автор ответа:
0
Пошаговое объяснение:
а)
5х + 3(х - 1) = 6х + 11
5х + 3х - 3 = 6х + 11
8х - 3 = 6х + 11
8х - 6х = 11 + 3
2х = 14
х = 14 : 2
х = 7
с)
8(у - 7) - 3(2у + 9) = 15
8у - 56 - 6у - 27 = 15
2у - 83 = 15
2у = 15 + 83
2у = 98
у = 98 : 2
у = 49
е)
6 + (2 - 4х) + 5 = 3(1 - 3х)
6 + 2 - 4х + 5 = 3 - 9х
13 - 4х = 3 - 9х
-4х + 9х = 3 - 13
5х = -10
х = -10 : 5
х = -2
Похожие вопросы
Предмет: Математика,
автор: bagmetovaveronika1
Предмет: Математика,
автор: adelzaynidin
Предмет: Литература,
автор: sasha44625
Предмет: Английский язык,
автор: sofiamopsik